PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA EMITEN SEKTOR PEROPERTY DAN REAL ESTATEYANG TERDAFTAR DI BEI - Putra, Farhan Hartono; Yusuf , Muhammad; Zairin, Gentiga Muhammad (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to determine the effect of Capital Intensity (X1), Inventory Intensity (X2), and Company Size (X3) on Tax Avoidance. The independent variables in this research are Capital Intensity with Capital Intensity Ratio, Inventory Intensity with Inventory Intensity Ratio, Company Size with Total Assets, the Dependent Variable in this research uses Tax Avoidance which is measured using the Effective Tax Rate indicator. The method used in this research is quantitative using secondary data sourced from financial reports throughout the Peroperty and Real Estatesector for the 2017-2021 period. The sampling method in this research used a purposive sampling method with 240 observations. This research uses a panel data regression analysis method processed with the Eviews 12 application. The results obtained from this study indicate that Capital Intensity and Inventory Intensity do not have an effect on Tax Avoidance, while Company Size has an effect on Tax Avoidance.